A Health Economic Analysis Exploring the Cost Consequence of Using a Surgical Site Infection Prevention Bundle for Hip and Knee Arthroplasty in Germany - Rhodri Saunders; Rafael Torrejon Torres; Henning Reuter; Scott Gibson (Journal of Health Economics and Outcomes Research)
# Background